Microbial lipids reveal carbon assimilation patterns on hydrothermal sulfide chimneys. (7th July 2014) - Reeves, Eoghan P.; Yoshinaga, Marcos Y.; Pjevac, Petra; Goldenstein, Nadine I.; Peplies, Jörg; Meyerdierks, Anke; Amann, Rudolf; Bach, Wolfgang; Hinrichs, Kai‐Uwe
Summary Sulfide 'chimneys' characteristic of seafloor hydrothermal venting are diverse microbial habitats. 13C/12C ratios of microbial lipids have rarely been used to assess carbon assimilation pathways on these structures, despite complementing gene‐ and culture‐based approaches. Here, we integrate analyses of the diversity of intact polar lipids (IPL) and their side‐chain δ13C values (δ13Clipid) with 16S rRNA gene‐based phylogeny to examine microbial carbon flow on active and inactive sulfide structures from the Manus Basin. Surficial crusts of active structures, dominated by Epsilonproteobacteria, yield bacterial δ13Clipid values higher than biomass δ13C (total organic carbon), implicating autotrophy via the reverse tricarboxylic acid cycle. Our data also suggest δ13Clipid values vary on individual active structures without accompanying microbial diversity changes. Temperature and/or dissolved substrate effects – likely relating to variable advective–diffusive fluxes to chimney exteriors – may be responsible for differing 13C fractionation during assimilation. In an inactive structure, δ13Clipid values lower than biomass δ13C and a distinctive IPL and 16S rRNA gene diversity suggest a shift to a more diverse community and an alternate carbon assimilation pathway after venting ceases. We discuss here the potential of IPL and δ13Clipid analyses to elucidate carbon flow in hydrothermal structures when combined with other molecular tools.